In-situ thermally fabricated porous and heterogeneous yolk-shell selenides wrapped in carbon as anode for high-performance hybrid lithium-ion capacitors. (30th September 2020) - Chen, Daming; Sun, Shangqi; Yu, Genxi; Qin, Liguang; Wang, Weijuan; Jiang, Mingyue; Chen, Jian
Abstract: Lithium-ion capacitors (LICs) are a relatively new hybrid system that combines the merits of Faradaic and capacitive behaviors, demonstrating great potentials in modern applications. However, the mismatch in reaction kinetics between these two types of electrode materials, the slow Faradaic reaction in the battery anode and the rapid adsorption/desorption process in the capacitor cathode, severely restricts the application of LICs. In this study, the porous yolk-shell selenide frameworks (ZnSe@CoSe2 ) are constructed using the core-shell ZIF-8@ZIF-67 as precursor by a sequential thermal program. Detailed morphological investigation discloses that the yolk-shell structure is in-situ formed during the early incubation at lower temperature. The yolk-shell ZnSe@CoSe2 frameworks in an N-doping carbon layer (Z@C@P) as the anode material for lithium-ion batteries, which exhibits high rate capability and good cycle stability at a high current density of 2 A/g, which greatly bridges the kinetic gap with the capacitor-type electrode. Thereby, the assembled LICs with active carbon show high energy density, power density and capacity retention rate. To the best of our knowledge, the selenides are firstly used as anode material for LICs with such extraordinary performance, and the unique structural and compositional design strategies can also benefit the development of high-performance electrodes for energy-storage devices. Graphical abstract: Image 1